Analysis of Digital Marketing Implementation for Kue Pancong Lumer and Jumbo Iced Tea MSMEs at Polbeng Business Expo Chapter II - Erni Suraya (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the implementation of digital marketing for Kue Pancong Lumer and Jumbo Iced Tea, two local micro, small, and medium enterprises participating in Polbeng Business Expo Chapter II. The study used a descriptive project-based case approach. Data came from observation, business profiling, project logbooks, social media content, sales records, financial statements, and activity documentation. The intervention covered the creation of 30 promotional videos, 30 digital product catalogs, social media publication, QRIS registration, and basic bookkeeping assistance. The results show that the project produced practical digital assets, strengthened product presentation, supported cashless transactions, and improved the availability of structured financial information. During the three-day expo on May 20-22, 2025, Kue Pancong Lumer recorded revenue of IDR 971,000, while Jumbo Iced Tea recorded IDR 400,000. May 2025 financial reports showed net profit of IDR 4,778,000 for Kue Pancong Lumer and IDR 5,675,000 for Jumbo Iced Tea. These outcomes indicate that integrated digital promotion, transaction digitalization, and financial recording can strengthen MSME readiness for market expansion. However, the study did not use a control group or pre-intervention digital performance metrics. The findings therefore describe implementation outcomes and business readiness rather than a direct causal effect. The project also confirms the strategic value of collaboration between higher education institutions and local MSMEs in applying digital business practices.